A facile PCR‐RFLP method for genotyping of ITPA rs1127354 and rs7270101 polymorphisms. Issue 7 (16th April 2018) - Alavian, Seyed Ehsan; Sharafi, Heidar; Shirmast, Paniz; Alavian, Seyed Moayed; Behnava, Bita; Pouryasin, Mohammad; Keshvari, Maryam; Pouryasin, Ali
Abstract : Background: Inosine triphosphate pyrophosphatase ( ITPA ) gene single nucleotide polymorphisms (SNPs), rs1127354 and rs7270101, may cause a functional impairment in ITPase enzyme, resulting anemia protection in patients with chronic hepatitis C virus (HCV) infection undergoing ribavirin (RBV)‐dependent regimens. The main purpose of this study was to provide and validate a simple, rapid, and inexpensive polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP) technique for genotyping of ITPA rs1127354 and rs7270101 polymorphisms in chronic HCV‐infected patients. Methods: In the current study, 100 Iranian patients with chronic hepatitis C were examined and genotyped for ITPA rs1127354 and rs7270101 gene polymorphisms. To genotype rs1127354 and rs7270101 polymorphisms, PCR‐RFLP technique and sequencing technique were performed on these samples. To validate the PCR‐RFLP method, the PCR‐RFLP genotyping results should be 100% concordant with the PCR‐sequencing results. Results: The rs1127354 and rs7270101 polymorphisms of ITPA gene were genotyped by PCR‐RFLP technique and sequencing simultaneously, and the results of both techniques were 100% concordant in all 100 patients. Both PCR‐RFLP and sequencing techniques indicated that the genotypic frequency of rs7270101 was 80% AA, 19% AC and 1% CC, and for rs1127354 was 79% CC, 20% CA and 1% AA, respectively. Conclusion: We developed and validated a rapid and inexpensive PCR‐RFLP technique for the detection of ITPA rs1127354 and rs7270101 gene polymorphisms.